The situation of low vision services in Papua New Guinea: an exploratory study. (1st September 2016) - Marella, Manjula; Yu, Mitasha; Paudel, Prakash; Michael, Alois; Ryan, Kevin; Yasmin, Sumrana; Minto, Hasan
Abstract: Background: The aim of this study was to investigate the current situation of low vision services and barriers to low vision service delivery in Papua New Guinea (PNG). Methods: An exploratory study was undertaken to assess the situation of available services, human resources, training, equipment and assistive devices, supportive policies, needs of people with low vision and community attitudes toward people with low vision. In‐depth interviews with 50 key informants were conducted in‐country. Key informants included eye‐care practitioners (n = 13), special education teachers (n = 10), community‐based rehabilitation workers (n = 3), other stakeholders providing disability‐related services (n = 8), and people with low vision (n = 14) and their family members (n = 2). Interview transcripts were analysed inductively and deductively using thematic analysis. Results: Barriers were identified at systems and community levels. The barriers at the systems level were: low vision not a priority area for eye care and rehabilitation programs, limited availability of low vision services, trained personnel and low vision devices; low vision not included in training programs of eye‐care practitioners and lack of awareness of available referral services among service providers. The barriers identified at the community level were lack of awareness of services, distance, costs and limited transport to access services and negative community attitudes. Conclusion: This study has identified barriers from the perspectives of different stakeholders, including service providers and people with low vision and their families. Knowledge of these barriers can now guide the development of future low vision services in PNG.